1981
DOI: 10.1536/ihj.22.151
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of QT prolongation and T wave changes in chronic alcoholism.

Abstract: SUMMARYEtiology of QT prolongation and T wave high voltage was studied in 90 chronic alcoholics in relation to history of alcoholism, blood chemical values, heart rate and QRS voltage with a technic of multiple regression analysis. Incidences of QT prolongation (22%), T wave high voltage in lead V2 (9%), hypopotassemia (23%), hypocalcemia (26%) and hypomagnesemia (28%) were high, despite these examinations were done after relatively long abstention period (35 days on average). Sinus tachycardia (19%) and QRS h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
1
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
2
6
1
1
Order By: Relevance
“…It was not related to the electrolyte level. It is a higher frequency than the one found in two Japanese studies: Koide et al (1981) found it in 22% and Yokoyama et al (1992) in 46.9% of the examinees.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…It was not related to the electrolyte level. It is a higher frequency than the one found in two Japanese studies: Koide et al (1981) found it in 22% and Yokoyama et al (1992) in 46.9% of the examinees.…”
Section: Discussioncontrasting
confidence: 57%
“…In the study of Koide et al (1981), a correlation with serum electrolyte level was not found. Our findings also correspond with the data of Day et al (1993).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, in that study, the associated/confounding factor was hypomagnesemia stated by authors. The correlation between alcoholism and extended QTc interval has also been confirmed by other studies [20][21][22][23] . In the study of Bär et al 24 , a statistically significant prolongation of QTc interval in male persons with the symptoms of alcoholic abstinence (n = 18) in relation to the "pair matched" control group was established, but not in the case of syndrome of dependence without the abstinence syndrome (n = 15).…”
Section: Discussionsupporting
confidence: 78%